Characterization and Evaluation of Soils of Singanallur Watershed Using Remote Sensing and GIS - Vasundhara, R.; Dharumarajan, S.; Hegde, Rajendra; Srinivas, S.; Niranjana, K. V.; Srinivasan, N.; Singh, S. K. (International Journal of Bio-resource and Stress Management, 2023)
Watershed is an ideal unit calling for multidisciplinary approach to the resources management for ensuring continuous benefit on sustainable basis. Land Resource mapping plays a vital role in resource management. A detailed soil survey is planned for the Singanallur micro watershed, Kollegal taluk, Chamaraj nagar district, Karnataka by using cadastral map overlaid on Cartosat-1(ortho corrected)+LISS IV image as a base to characterize and classify the land resources. Based on elevation and slope, three physiographic units were identified namely gently sloping lands (3–5%) very gently sloping lands (1–3%) and nearly level lands (0–1%). Soil profile study was carried out to identify the problems and potentials of the land resources. Based on morphological and physiochemical properties, six soil series were identified and the study area was delineated into 25 management units. Taxonomically, these soil series were grouped under Alfisols (Typic Rhodoustalfs and Rhodic Paleustalfs) and Inceptisols (Typic Haplustepts). The site evaluation of the soils showed that nearly 50% of the watershed area is highly suitable for ragi, maize, onion, turmeric and banana. More than 70% area is moderately to marginally suitable for red gram and groundnut due texture limitation. Different land use options and suitable interventions were suggested based on the potentials and limitations of the watershed area. This baseline data helps to monitor the different development programmes for enhancing the agricultural production.